Effect of extracts from Sapindus saponaria on the glasshouse whitefly Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - PORRAS, MITZY F.; LÓPEZ-ÁVILA, ARISTÓBULO (Revista Colombiana de Entomología, 2009)
The glasshouse whitefly, Trialeurodes vaporariorum, causes economic losses on several crops in the world. In Colombia, bean, green bean, tomato and other crops are severely affected by this insect. In the search for tools to control the whitefly, natural extracts have been presented as one alternative, since they are compounds with lethal and sublethal effects on insects. Among these are the saponins from Sapindus saponaria, which is present in the Neotropics and grows in dry and humid forests. In the present research a colony of whiteflies from the entomology laboratory of Corpoica in C.I-Tibaitatá was established on ICA Pijao beans. The experiments were carried out under controlled conditions with a temperature of 16ºC and a relative humidity of 80%. The effects of the crude and the semi-purified extracts from S. saponaria on whitefly adults were evaluated at concentrations of 100, 200, 400, 800 and 1000 ppm. The insect mortality was recorded 24 hours after the application of the treatments and the mean lethal dose (LD50) was determined by Probit analysis. The mean lethal dose for the crude extract was established at 203 ppm, and at 88 ppm for the semi-purified extract.